A cybertaxonomic revision of the new dung beetle tribe Parachoriini (Coleoptera: Scarabaeidae: Scarabaeinae) and its phylogenetic assessment using molecular and morphological data - Tarasov, Sergei (Zootaxa, 2017)
Two Oriental dung beetle genera: Parachorius Harold, 1873 and Cassolus Sharp, 1875 have long had an ambiguous tribal position in Scarabaeinae (Coleoptera: Scarabaeidae), but have never been considered as closely related. A recently discovered species representing the morphological link between the two genera gave a hint to their possible close affiliation. To assess phylogenetic and taxonomic placement of these genera, I conducted phylogenetic analyses of global dung beetle samples using morphological (134 taxa, 232 characters) and molecular (551 terminals, 8 gene regions) data. Both morphological and molecular analyses strongly support the monophyly of Parachorius + Cassolus. This leads to the synonymy of Parachorius with Cassolus new synonymy, and resulted in the new generic concept for Parachorius. The isolated phylogenetic position of Parachorius and its morphological distinctiveness from all other known Scarabaeinae tribes suggest recognition of a new tribe, Parachoriini new tribe, to maintain the stability of tribal classification in dung beetles. Investigation of old and recent material of Parachorius revealed a large number of undescribed species and the need for a taxonomic revision of this genus. The revision of Parachorius, powered by the 3i cybertaxonomic tool, is presented in this study. The revised Parachorius is comprised of 19 species from the Oriental and southeastern Palaearctic Regions, of which seven are newly described (P. asymmetricus new species, P. bolavensis new species, P. longipenis new species, P. newthayerae new species, P. pseudojavanus new species, P. schuelkei new species, and P. solodovnikovi new species). Three species names in Parachorius are synonymized, namely, P. fungorum Kryzhanovsky & Medvedev, 1966 = P. krali Utsunomiya & Masumoto, 2001 new synonymy; P. thomsoni Harold, 1873 = P. lannathai Hanboonsong & Masumoto, 2001 new synonymy; and P. peninsularis (Arrow, 1907) = C. pongchaii Masumoto, 2001 new synonymy. Two species originally described in Cassolus (C. sumatranus and C. minutus) are transferred to the genus Panelus Lewis, 1895. The rank of the genus Macropanelus is lowered to a subgenus within Panelus (i.e. Panelus (Macropanelus) new status).